Pengaruh Social Media Marketing dan Brand Awareness Terhadap Keputusan Pembelian Skintific di Shopee - Daffa Mahendra; Rudy P. Tobing (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Background: The advancement of digital technology has transformed how consumers interact with brands, including in the skincare industry. Social media, particularly Instagram, has become an effective platform to enhance brand awareness and influence purchasing decisions. This study aims to analyze the effect of social media marketing and brand awareness on the purchasing decisions of Skintific products on Shopee, a leading e-commerce platform in Indonesia.Design/methodology/approach: This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 97 respondents who met specific criteria, such as having purchased Skintific products on Shopee. The data were analyzed using multiple linear regression with SPSS software to examine the influence of independent variables on the dependent variable.Results: The findings reveal that social media marketing and brand awareness have a positive and significant impact on consumers' purchasing decisions. Social media marketing, through engaging and interactive content, effectively increases consumer interest, while brand awareness strengthens product image in consumers' minds, encouraging them to make purchases.Research limitations/Implications: This study has several limitations, such as being limited at Jakarta and having a relatively small sample size, making the results less generalizable to all consumers in Indonesia. The implications of this research provide insights for skincare business practitioners about the importance of digital marketing strategies, particularly through social media, to boost sales.